Mephistopheles' Atopy, Allotry, Lottery. On textual proliferations in Goethe's Faust I and II - Pasqual Solass (Vernacular: New Connections in Language, Literature, & Culture, 2022)
Combining a careful reading of selected passages from Goethe’s Faust I and II and of marginal but nevertheless revealing lines on maybe the actual protagonist of the “Tragödie”, Mephistopheles, this paper aims to present aspects of what one could call Goethe’s vision of a modern devil. Taking departure from etymological considerations on the root of “diabolus”, i.e. diabállein, meaning to cast apart, to scatter, but also to accuse, as well as from different beliefs of German “Aberglaube” (superstition), it will become clear that one if not the major feature of Goethe’s Mephistopheles-figure is movement, not just in the spatial, but also in the temporal sense: Mephistopheles enacts different sediments of the devils cultural history and even travels to the mythical time of antiquity where something like a devil did not exist (atopia). Other than that, Mephistopheles always appears as an-other (allotria), no concept or principle seems to capture him, he does not appear to coincide with himself. Rather he incessantly multiplies “himself”, as his names are “legion”, constantly casting doubt on his plans, his identity, his site, not least as appearance itself (“Schein”), when he generates paper money (“Geldscheine”) and thus creates new means of apparent or rather virtual movement for the Kaiser in Faust II – cash flow.